18.2k views
1 vote
The expression is the result of applying the change of base formula to a logarithmic expression.

Which could be the original expression?

The expression is the result of applying the change of base formula to a logarithmic-example-1
User Loxdog
by
5.2k points

2 Answers

6 votes

x= 8 is the correct answer

User Linens
by
4.6k points
3 votes

Answer:

x = 8

Explanation:

Given equation is,


log_5(10x-1)=log_5(9x+7)

We know that,


log_a(b)=log_a(c)\implies b = c


\implies 10x -1 = 9x + 7

Subtracting 9x on both sides,


x - 1 = 7

Adding 1 on both sides,


x = 8

Hence, the solution would be x = 8

User Wige
by
4.8k points